Utilização da cal e da cinza da casca de arroz no melhoramento das propriedades geotécnicas de solos - Klamt, Rodrigo André (2012)
The research reported here in this assignment aimed to study the technical feasibility of stabilizing a sandy soil from Alegrete/RS with the addition of lime and rice husk ash. The limes are widely used in soil’s improvement, the difference is the inclusion of percentages of CCA, which is in the group of large volume generated annually and are often improperly discarded into the environment without any technical criterion, or demand high costs relating to storage and final disposal. The methodology of the study was to develop a program of experimental tests that allowed the know ledge and improvement of some properties in the sandy soil from a deposit located in the city of Alegrete, RS, with the use of different percentages of lime and CCA as stabilizing agents. The body-proof’s results were compared without any stabilizer samples with different amounts of these materials and, thus, is proven performance of the different traits studied. Particle size test, consistency of limits, compaction and compression strength (RCS) were realized. The same characteristics in all studied sample were found and it was possible to determined the influence so curing time and contents of lime and lime+CCA in the compressions, resistors and characterizations. The maximum values of compressive strength were obtained for mixtures with lime+CCA. The stabilization of a sandy soil with limes and CCA proved it selves effective, allowing the use of these materials in the layers of the base and sub-base for paving, in order to add new materials and minimizing the problem of disposal of rice hull ash.